COVID-19-related stress, anxiety and vaccine hesitancy among healthcare workers in a tertiary hospital in South-Western Nigeria - Temitope Olumuyiwa Ojo; Tajudin Adesegun Adetunji; Stanley Chinedu Eneh; Baderinwa Opeyemi Akanji; Olusola Fajobi; Olanrewaju Elugbaju; Olanrewaju Ibikunle Ibigbami; Temilola Oladunmomi Owojuyigbe; Samuel Anu Olowookere; Olusegun Temitope Afolabi; Adedeji Ayodeji Onayade (Scientific Reports)
Abstract COVID-19 ranks as one of the major pandemics in recent history, with healthcare workers disproportionately burdened by the disease. Vaccination emerged as the most effective measure to curb the spread and reduce COVID-19 morbidity and mortality. However, vaccine hesitancy presents a challenge to achieving optimal vaccination coverage in Nigeria. This study assessed the level of COVID-19-related stress and anxiety as well as factors associated with vaccine hesitancy among healthcare workers. A descriptive, cross-sectional study was conducted among 849 health workers of a tertiary hospital. Vaccine hesitancy, COVID-19 related stress and anxiety were assessed using the Vaccine Hesitancy Scale (VHS) and SAVE-6 scale respectively. Also, the WHO-5 index was used to assess the perceived mental wellbeing among study participants. Data analysis was conducted using SPSS 25 at univariate, bivariate and multivariate levels. There were slightly more males (479; 56.4%) than females and about four-fifth (674; 79.4%) of respondents were married. About one-quarter of health workers were vaccine hesitant, 236 (27.8%) while 96 (11.3%) had high levels of stress and anxiety. Also, 38 (4.5%) of respondents had poor mental wellbeing. Females when compared to males, had significantly higher odds (OR 1.50; 95% CI 1.10–2.10; p = 0.023) of having vaccine hesitancy while those who were married compared to their single counterparts had significantly lesser odds (OR 0.60; 95% CI 0.36–0.94; p = 0.026). However, there was no significant association between COVID-19 related anxiety and vaccine hesitancy. COVID-19 vaccine hesitancy exists even among health professionals. This study highlights that gender and marital status significantly influence vaccine hesitancy among healthcare workers. Healthcare workers need to receive vaccines to protect themselves and others. Given their role in educating patients and community members about vaccination against infectious diseases like COVID-19, targeted interventions are needed to address hesitancy and optimize vaccine acceptance among healthcare professionals.